The Mindgym : Relationships - The Mind Gym (London Sphere, 2010)
Whether it's the boss, clients, friends or lovers, getting relationships right matters. This book shows how to make yours shine. Drawing on the latest research and the experience of 500,000 people who use the Mind Gym system, this book reveals how to: be loved, respected and even obeyed; build trust in moments that lasts for years; turn an angry argument into an unbreakable bond; get on with people who don't get on with anyone else; and repair a broken relationship so it's stronger than ever.
Include Pictures, Bibliography and Index
Keywords: Interpersonal relations. -- Self-actualization (Psychology)